Equitable Islamic Education Through Leadership: A Managerial Model of a Tahfidz Boarding School for the Underprivileged - Hasbar, Hasbar; Warman, Warman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study examines the development of effective leadership models for promoting educational equity in tahfidz boarding schools serving underprivileged communities. Using a Literature Systematic Review (LSR) methodology, this research analyzed 92 peer-reviewed articles from 2021-2025 to identify key leadership competencies, organizational structures, and management practices that enable Islamic educational institutions to deliver equitable education while maintaining religious authenticity. Five research questions guided the investigation, focusing on leadership characteristics, Islamic-modern integration, organizational effectiveness, student challenges, and comprehensive managerial models. The findings reveal five core leadership competencies: transformational leadership, instructional leadership, cultural competency, moral integrity, and adaptive innovation capacity. The study identifies effective integration mechanisms between Islamic principles and contemporary management practices, including values-based systems, community-centered governance, and holistic development frameworks. Key organizational structures include distributed leadership, community-based governance, integrated support services, and flexible financial management systems. The research addresses primary challenges facing underprivileged students, including academic preparation disparities, socioeconomic stress, cultural adjustment issues, mental health concerns, and career preparation needs. Based on these findings, the study proposes the Integrated Islamic Educational Leadership (IIEL) Model, consisting of five interconnected components that provide a comprehensive framework for establishing and sustaining equitable tahfidz boarding schools. This model offers practical guidance for educational leaders, policymakers, and community stakeholders seeking to develop Islamic educational institutions that effectively serve underprivileged populations while maintaining educational excellence and spiritual authenticity.